Climate Change and Environmental Degradation: A Threat to Global Security - Osawe, Anthony Ikhide (African Journal of Stability and Development (AJSD), 2019)
There is the global recognition that climate change and environmental degradation are caused by human activities which have considerably increased the atmospheric concentration of greenhouse gases. The consequences of climate change are: droughts which adversely affect the global poor who are engaged in agriculture; storm surges which destroy local infrastructures, housing and farm crops; and the rise of sea levels which adversely affect the inhabitants of small island states which could eventually be totally submerged. The implication is that an indefinite number of people are displaced. The serious repercussion for international security is that the world will very soon be flooded with climate refugees with no legal status under the Geneva Convention. Three urgent responses are required: (i) consideration of the right of future generations not to suffer from the adverse effects of climate change, (ii) assessing the relevant conceptions of global justice, and (iii) examination of existing protocols and international laws that provide effective defensive responses to climate change and attainment of sustainable environmental security and global peace.